DNA interstrand cross-link repair in Saccharomyces cerevisiae. - Lehoczký, P; McHugh, P; Chovanec, M (2007)
DNA interstrand cross-links (ICL) present a formidable challenge to the cellular DNA repair apparatus. For Escherichia coli, a pathway which combines nucleotide excision repair (NER) and homologous recombination repair (HRR) to eliminate ICL has been characterized in detail, both genetically and biochemically. Mechanisms of ICL repair in eukaryotes have proved more difficult to define, primarily as a result of the fact that several pathways appear compete for ICL repair intermediates, and also because these competing activities are regulated in the cell cycle. The budding yeast Saccharomyces cerevisiae has proven a powerful tool for dissecting ICL repair. Important roles for NER, HRR and postreplication/translesion synthesis pathways have all been identified. Here we review, with reference to similarities and differences in higher eukaryotes, what has been discovered to date concerning ICL repair in this simple eukaryote.